2019
DOI: 10.3758/s13415-019-00747-7
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of aversive anticipation: An activation likelihood estimate meta-analysis across multiple sensory modalities

Abstract: Anticipation is a universal preparatory response essential to the survival of an organism. Although meta-analytic synthesis of the literature exists for the anticipation of reward, a neuroimaging-based meta-analysis of the neural mechanisms of aversive anticipation is lacking. To address this gap in the literature, we ran an activation likelihood estimate (ALE) meta-analysis of 63 fMRI studies of aversive anticipation across multiple sensory modalities. Results of the ALE meta-analysis provide evidence for a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Some previous work suggests left laterality in dlPFC function during threat anticipation, 42,57 although such associations do not arise consistently. 20 Additional research is required to determine asymmetry in prefrontal cortex structural correlates of anticipatory response. We also reported novel associations between the thickness of the posterior insula and psychophysiological response to pain.…”
Section: E219mentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous work suggests left laterality in dlPFC function during threat anticipation, 42,57 although such associations do not arise consistently. 20 Additional research is required to determine asymmetry in prefrontal cortex structural correlates of anticipatory response. We also reported novel associations between the thickness of the posterior insula and psychophysiological response to pain.…”
Section: E219mentioning
confidence: 99%
“…This work has implicated networks such as the insular and prefrontal cortices, as well as connected limbic structures. 4,8,10,[18][19][20][21] Such studies have primarily contrasted neural function during anticipation with safety conditions; relatively few studies have directly linked brain function to anticipatory psychophysiological response (e.g., Seifert and colleagues, 10 Wendt and colleagues 22 and Gu and colleagues 23 ), presenting a gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Not taking into account the dimension of control, there is a consistent body of research referring to the neural basis of the anticipation and the processing of aversive stimulation. A recent meta‐analysis of the neural correlates of aversive anticipation identified a core circuit including the anterior insula, the anterior cingulate cortex (ACC), the midcingulate cortex (MCC), the amygdala, thalamus, and caudate nucleus (Andrzejewski et al, 2019 ). Many of these regions overlap with areas identified as being crucial for the anticipation of rewards (Gu et al, 2019 ; X. Liu, Hairston, Schrier, & Fan, 2011 ; Wilson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the actual processing of aversive stimulation, Hayes and Northoff ( 2011 ) showed that the most consistent findings across both human and animal studies demonstrate the implication of the amygdala, the anterior insula, the ventrolateral orbitofrontal cortex, and the rACC. Both of these meta‐analyses on the anticipation and the processing of aversive stimulation (Andrzejewski et al, 2019 ; Hayes & Northoff, 2011 ) considered studies using different sensory modalities. So far, only few studies have used auditory aversive stimuli (Bolstad et al, 2013 ; Carlson, Greenberg, Rubin, & Mujica‐Parodi, 2011 ) despite of the potential that auditory stimulation hold for experimental tasks, for example, in the context of fMRI with humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation